If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -2 = 5x + 34 Reorder the terms: -2 + 9x = 5x + 34 Reorder the terms: -2 + 9x = 34 + 5x Solving -2 + 9x = 34 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -2 + 9x + -5x = 34 + 5x + -5x Combine like terms: 9x + -5x = 4x -2 + 4x = 34 + 5x + -5x Combine like terms: 5x + -5x = 0 -2 + 4x = 34 + 0 -2 + 4x = 34 Add '2' to each side of the equation. -2 + 2 + 4x = 34 + 2 Combine like terms: -2 + 2 = 0 0 + 4x = 34 + 2 4x = 34 + 2 Combine like terms: 34 + 2 = 36 4x = 36 Divide each side by '4'. x = 9 Simplifying x = 9
| 6(x+1.34)=5x | | 5(t+2)=2t+25 | | -3.05=7.24-3.5t | | 5(t-2)=2t+25 | | 7p+7=q-p | | -4.2x+3.04=-4.1 | | lg(x)+lg(x-1)=lg(2) | | 0.20(5-n)-0.50(5)= | | 6(x-5)=2(x+43) | | 0.20(5-n)= | | 5x+2x-7x=7 | | 7-8-(-5)-1= | | 5-n=n-5 | | 0.20(5-n)=0.50(5) | | 0.20(5-n)-1.00=0.50(5) | | 4x+2x+2x+4x+6=10+4+18 | | 7n+6=3n+20 | | (4x-5)(x+2)=0 | | iz^2+3z+4i=0 | | 3x+7=2(3+4) | | 7(x-2)-4=5x+20 | | 2x+3y=86 | | 10x-2x+20=4(2x+5) | | 6.40(9)+7.28p=6.40(9+p) | | 51x-12x+(56-4)=94x+34 | | Z^3+3Z+5=0 | | 6.40(9)-7.28p=6.40(9+p) | | (4x-5)(x+2)=12 | | 14x+82=86x-2 | | 10x+25=5x-10 | | (X-12)+(2x+18)=180 | | 4x+2x+6x+2+4+6=8+2+10 |